The Key Role of c-Fos for Immune Regulation and Bacterial Dissemination in Brucella Infected Macrophage - Hop, Huynh T.; Arayan, Lauren T.; Huy, Tran X. N.; Reyes, Alisha W. B.; Vu, Son H.; Min, WonGi; Lee, Hu J.; Rhee, Man H.; Chang, Hong H.; Kim, Suk (Frontiers in Cellular and Infection Microbiology, 2018)
The cellular oncogene c-Fos (c-Fos) is a component of activator protein 1 (AP1), a master transcriptional regulator of cells. The suppression of c-Fos signaling by siRNA treatment resulted in significant induction of TLR4, which subsequently activates p38 and ERK1/2 mitogen-activated protein kinases (MAPKs) and enhances F-actin polymerization, leading to an increase in B. abortus phagocytosis. During B. abortus infection, c-Fos signaling is induced, which activates the downstream innate-immunity signaling cascade for bacterial clearance. The inhibition of c-Fos signaling led to increased production of interleukin 10 (IL-10), which partially suppressed lysosome-mediated killing, resulting in increased survival of B. abortus inside macrophages. We present evidence of the regulatory role played by the c-Fos pathway in proliferation during B. abortus infection; however, this was independent of the anti-Brucella effect of this pathway. Another finding is the essential contribution of c-Fos/TRAIL to infected-cell necrosis, which is a key event in bacterial dissemination. These data provide the mechanism via which c-Fos participates in host defense mechanisms against Brucella infection and in bacterial dissemination by macrophages.